Successful powerlifting in a unilateral, transtibial amputee: A descriptive case series - Beausejour, J. P.; Guinto, G.; Artrip, C.; Corvalan, A.; Furtado Mesa, M.; Lebron, M. A.; Stock, M. S. (The Journal of Strength and Conditioning Research, 2024)
There are no reports in the literature of powerlifting success after amputation. We had the unique opportunity to characterize functional outcomes, strength, muscle contractility and size, and corticospinal excitability in an accomplished, competitive powerlifter (best competition squat = 205.0 kg, deadlift = 262.7 kg) with a unilateral, transtibial amputation relative to amputee controls. Four men (age range = 23-49 years) with unilateral, lower-limb amputation (3 transtibial, 1 transfemoral) participated in 1 laboratory visit. We assessed 10-m gait speed, the timed up and go (TUG) test, 5-time sit-to-stand performance (5TSTS), contractile properties of the vastus lateralis (VL) and medial gastrocnemius by tensiomyography, and VL cross-sectional area (CSA) by ultrasonography. Unilateral assessments for the intact limb included isokinetic knee extension and flexion torque and power and transcranial magnetic stimulation derived corticospinal excitability. An interview with the powerlifter provided contextual perspective. Compared with the control subjects, the powerlifter performed the 5TSTS faster (6.8%), exhibited faster VL contraction times (intact limb = 12.2%; residual limb = 23.9%), and showed larger VL CSA for the intact limb (46.7%). The powerlifter exhibited greater knee extension and flexion peak torque and mean power, particularly at 180°·s-1, as well as greater corticospinal excitability for the intact VL (65.6%) and tibialis anterior (79.6%). By contrast, the control subjects were faster in the TUG (18.3%) and comfortable (13.0%) and fast (21.4%) in the 10-m walk test. The major themes of our interview included needing to modify lifting mechanics, persistence, and remarkable pain tolerance. Our findings highlight the impressive neuromuscular adaptations that are attainable after lower-limb amputation.